Analysis Potential of The Fisheries Sub-Sector in Improving GRDP Subang Regency - Alim, Fauzan Syaiful; Maulina, Ine; Rochima, Emma; Suryana, Asep Agus Handaka (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2024)
The aim of this study is to examine the impact of the fisheries sub-sector on the Gross Regional Domestic Product (GRDP) of Subang Regency by considering indicators of production output and labor force. To achieve this, descriptive analysis was employed on secondary data covering fisheries production output and labor force from the Subang Regency Fisheries Department for the period from 2018 to 2022. Furthermore, this data was analyzed using multiple linear regression analysis using the SPSS program. The results indicate that the variable of fisheries production output partially does not have a significant impact on the GRDP of Subang Regency. Nevertheless, there are several prominent commodities in this sub-sector, including milkfish (Chanos chanos), mackerel (Decapterus sp.), snake mackerel (Trichiuridae sp.), ponyfish (Leiognathidae sp.), scad (Atule mate), sardines (Sardina pilchardus), hilsa shad (Tenualosa macrura), squid (Loligo sp.), and cuttlefish (Sepiida sp.) in marine capture fisheries; (ii) tilapia (Oreochromis mossambicus), catfish (Clariidae sp.), and carp (Cyprinus carpio) in inland capture fisheries; (iii) tilapia (Oreochromis mossambicus), milkfish (Chanos chanos), milkfish (Moolgarda seheli), snapper (Lutjanus sp.), and seaweed (Eucheuma spinosum).